Anti-N-methyl-D-aspartate receptor encephalitis after coronavirus disease 2019: A case report and literature review. Issue 35 (2nd September 2022) - Lee, Hyesun; Jeon, Jong Hyun; Choi, Hojin; Koh, Seong-Ho; Lee, Kyu-Yong; Lee, Young Joo; Kwon, Hyuk Sung
Abstract : Rationale: Coronavirus disease 2019 (COVID-19) has become a global pandemic and COVID-19-associated anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis may occur through an immune-mediated pathomechanism. Patient concerns: A 21-year-old woman with a history of COVID-19 presented to our hospital with memory decline and psychiatric symptoms. Diagnosis: The patient was diagnosed with anti-NMDAR encephalitis. Intervention: Intravenous methylprednisolone (1 g/day over 5 days) followed by immunoglobulin (0.4 g/kg/day over 5 days) were administered. The patient underwent laparoscopic salpingo-oophorectomy to remove an ovarian teratoma. Outcomes: The patient was discharged with sequelae of short-term memory impairment, without other neuropsychiatric symptoms. Lessons: Cases of previously reported anti-NMDAR encephalitis with COVID-19 were reviewed and compared with the present case. Clinicians should be aware of the occurrence of anti-NMDAR encephalitis in patients who present with neuropsychiatric complaints during or after exposure to COVID-19. Further studies are required to determine the causal relationship between the 2 diseases and predict the prognosis of anti-NMDAR encephalitis after COVID-19 exposure.